Dramatic effect in passive ROM exercise under sedation in a patient with intractable complex regional pain syndrome (type I): A case report. Issue 13 (March 2019) - Oh, Hyun-Min; Kim, Chul-Hyun; Kim, Ae-Ryoung
Abstract: Rationale: Complex regional pain syndrome (CRPS) usually occurs after trauma and surgery but can also occur spontaneously. There are various known pathophysiology and treatment protocols for CRPS. However, there is no established treatment guideline. Although physical therapy is known as the first line treatment for CRPS, performing physical therapy is difficult due to severe pain. This case reports the first case with positive effect of physical therapy under sedation that allowed early physical therapy. Patient concerns: A 19-year old female had her right elbow area slightly hit by someone else, after which it began to swell and become more painful. Active and passive range of motion (ROM) of the right upper extremity gradually decreased through 3 months, and pain and edema worsened. Diagnoses: She had allodynia, nonpitting edema, temperature asymmetry, and trophic change in fingernails in the right upper extremity, which met the diagnostic criteria for CRPS. In the 3-phase bone scan, which is a specific tool to diagnose CRPS, there was trace uptake increase in the right elbow and wrist, indicating possibility of CRPS. Interventions: Despite conventional treatments such as pharmacologic and interventional therapies, neither pain nor edema subsided. Pain was so severe that it was impossible to apply physical therapy. Therefore, the patient underwent passive ROM exercise in the right upper extremity under sedation for 30 minutes, which was relatively easier due to decreased pain. After 2 days of passive ROM exercise under sedation, the patient was able to receive passive ROM exercise twice daily without sedation for 18 days. Outcomes: After 20 days of passive ROM exercise, including 2 days of passive ROM exercise under sedation, the circumference of her right hand decreased by 5 cm, wrist 2 cm, and elbow 6 cm compared to the initial measurement. Numeric pain rating scale improved from 9 to 3, and her manual muscle test marked fair plus from trace, Jebsen–Taylor hand function test score 43 from 0. Lessons: This case suggests that passive ROM exercise under sedation may be a successful alternative as a treatment when exercise, currently known as a treatment to CRPS, is impossible.